TEACHER'S PERSPECTIVES ON THE USE OF READING COMPREHENSION STRATEGIES IN SMP NEGERI 35 MEDAN - Neni Afrida Sari Harahap; Ami Girsang; Marchel Sipahutar; Naufal Nasution; Ribka Manurung (Indonesian Journal of Education (INJOE), 2025)
This study aimed to explore the perspectives of an experienced English teacher on reading comprehension strategies at SMP Negeri 35 Medan. A descriptive qualitative design was employed to collect data through a semi-structured interview with a Year 9 English teacher with over fifteen years' experience. The findings revealed that the teacher employed student-centred strategies that emphasised higher-order thinking skills. These strategies included symbol and image-based learning, open-ended questioning, multimedia integration and flexible instructional adaptation. The selection of strategies was guided by students' learning styles, persistence, and readiness rather than by ability grouping. The study also identified key challenges in reading instruction, such as students' overreliance on digital tools without achieving genuine comprehension, and the limited availability of technological resources. Assessment practices focused on linguistic accuracy, particularly tense usage, and structural completeness, evaluated through various products, such as written texts, videos, and performances. The results showed that effective reading comprehension instruction in Indonesian English as a foreign language (EFL) contexts needs to balance cognitive demands with practical constraints, prioritising analytical and critical thinking over memorisation. This study sheds light on how experienced teachers navigate the complexities of reading instruction and provides practical implications for teacher development and instructional improvement in junior high school settings.